Reproduction Control Of Male Oreochromis Niloticus (Nile Tilapia) Using Gossypium Herbaceum (Cotton) Root Bark Meals As Fertility Inhibitor - B.J. Akin-Obasola; T. Jegede (European Scientific Journal, ESJ, 2016)
The study was carried out to control Tilapia population using Gossypium herbaceum root bark meal (GHRBM) as reproduction inhibitor. Gossypium herbaceum (Cotton) root bark meal was fed to male O. niloticus (31.38±0.67g). The root bark was added to a basal diet (35% crude protein) at 0, 5, 10, 15 and 20 g/kg diet. A total of 75 fishes were randomly distributed in triplicate into 15 plastic tanks (1x1x1m and 1.45 inches thick) at a stocking density of 5 fishes per 1m3. Groundwater of 400 litres volume was maintained throughout the period of experiment. The pH value was between 6.90 and 7.67, temperature ranged between 25.4 and 26.60C and dissolved oxygen concentration between 2.8 and 3.9 ml/l. The fish was fed at 4% body weight/day in two instalments at 09:00-09:30 hour and 17:00-17:30 hour. In fish fed 0g of GHRBM/kg diet, histological examination showed spermatocytes released into the lumen of the seminiferous tubules while in fish fed 5 g, 10 g, 15 g and 20 g GHRBM/kg diets, the sections showed eroded connective tissue, hydropic degeneration, disintegration in seminiferous lobule, damaged connective tissue and increased in interstitial cells. Except in the control treatment, it was observed that O. niloticus spermatozoa maintained normal morphology but low sperm count and low volume. Milt volume and milt count (P<0.05) decreased with increase in concentration of treatments used (from 0.5 to 0.1ml and 3.59 x109 to 0.33 x109 (Sperm/ml) respectively. Weight gained was highest in fish fed 10g GHRB/kg diet. It was observed that the feeding of Gossypium herbaceum root bark meals had no effect on water quality. Histological observations and milt analysis revealed that Gossypium herbaceum root bark may be effective as reproduction inhibitor in O. niloticus.